2022
DOI: 10.1111/jgs.17735
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic treatment deintensification practices in nursing home residents with type 2 diabetes

Abstract: Background Older nursing home (NH) residents with glycemic overtreatment are at significant risk of hypoglycemia and other harms and may benefit from deintensification. However, little is known about deintensification practices in this setting. Methods We conducted a cohort study from January 1, 2013 to December 31, 2019 among Veterans Affairs (VA) NH residents. Participants were VA NH residents age ≥65 with type 2 diabetes with a NH length of stay (LOS) ≥ 30 days and an HbA1c result during their NH stay. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
1
12
2
Order By: Relevance
“…[4][5][6][7][8] 8 We found higher rates of deprescribing compared to a recent study in US LTC homes, which may be explained by our longer follow-up period. 8 Limitations included missing HbA1c data for around 30% of residents with diabetes. We did not capture ethnicity, socioeconomic factors, and other factors that could affect T2DM management.…”
Section: Discussioncontrasting
confidence: 61%
“…[4][5][6][7][8] 8 We found higher rates of deprescribing compared to a recent study in US LTC homes, which may be explained by our longer follow-up period. 8 Limitations included missing HbA1c data for around 30% of residents with diabetes. We did not capture ethnicity, socioeconomic factors, and other factors that could affect T2DM management.…”
Section: Discussioncontrasting
confidence: 61%
“…All staff should be aware of the signs of hyperglycemia and hypoglycemia, which may be hard to spot in older patients or not be noticed at all 21 . Goals and Therapeutic Strategies Specifications: Recent research by Bouillet et al on 100 senior diabetic patients in Pakistani NHs found that 59% were using an oral anti diabetic medicine (OAD) alone, 42% were taking insulin alone, and 17% were taking both 59 . Similar results have been seen in other polls.…”
Section: Feet and Peripheral Neuropathymentioning
confidence: 99%
“…All staff should be aware of the signs of hyperglycemia and hypoglycemia, which may be hard to spot in older patients or not be noticed at all 21 . Goals and Therapeutic Strategies Specifications: Recent research by Bouillet et al on 100 senior diabetic patients in Pakistani NHs found that 59% were using an oral antidiabetic medicine (OAD) alone, 42% were taking insulin alone, and 17% were taking both 59 . Similar results have been seen in other polls.…”
Section: Comorbiditymentioning
confidence: 99%